2018
DOI: 10.1017/s0021859618000278
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment with glycine betaine enhances tolerance of cotton to chilling stress

Abstract: Chilling injury is an important natural stress that can threaten cotton production, especially at the sowing and seedling stages in early spring. It is therefore important for cotton production to improve chilling tolerance at these stages. The current work examines the potential for glycine betaine (GB) treatment of seeds to increase the chilling tolerance of cotton at the seedling stage. Germination under cold stress was increased significantly by GB treatment. Under low temperature, the leaves of seedlings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…[8,37,38]. It is involved in the protection of many plant species against a range of oxidative stress under stressful conditions, such as, salinity [39][40][41][42], drought [43][44][45][46], metal/metalloid stress [47][48][49], high temperature [45,50] and chilling [23,51,52]. A lot of research findings confirmed the positive relationship between accumulation of GB and plant stress tolerance.…”
Section: Variation Of Glycinebetaine Content In Plants Under Differenmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,37,38]. It is involved in the protection of many plant species against a range of oxidative stress under stressful conditions, such as, salinity [39][40][41][42], drought [43][44][45][46], metal/metalloid stress [47][48][49], high temperature [45,50] and chilling [23,51,52]. A lot of research findings confirmed the positive relationship between accumulation of GB and plant stress tolerance.…”
Section: Variation Of Glycinebetaine Content In Plants Under Differenmentioning
confidence: 99%
“…Pretreatment by GB improved the K + and Ca +2 nutrition, increased free Pro and GB content and levels of soluble sugars, which finally developed chilling stress (15 o C for 2 d) tolerance in sugarcane. Recently, Cheng et al [23] demonstrated that exogenous GB treatment of seeds increases the chilling tolerance of cotton at the seedling stage. Moreover, GB decreases the membrane damage and improves the antioxidant defense system in the cotton plant.…”
Section: Extreme Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Compatible solutes including polyamines, proline, GB, and soluble sugar accumulation in plants are positively correlated with low temperature stress tolerance [ 171 , 172 ] and extreme temperature [ 64 , 173 ] in plants. Glycine betaine enhanced the growth of potato [ 174 ], maize [ 175 ], chickpea ( Cicer arietinum L.) [ 176 ], and cotton [ 177 ] under chilling stress conditions. Cooling (<10 ℃) is particularly harmful to the development of chickpea, especially during the reproductive stage.…”
Section: Involvement Of Glycine Betaine Against Combinations Of Abmentioning
confidence: 99%
“…On the other hand, during pod filling, GB treatment resulted in an increase in the number of seeds and its yield, seed weight and pods were significantly improved after treatment. Glycine betaine greatly induced cold stress tolerance in plants through effective improvement in overall leaf water, sucrose and chlorophyll content, meanwhile, it also reduced the ROS and contents of abscisic acid as well [ 177 ]. Some plant species such as barley ( Hordeum vulgare L.) [ 179 ] and spinach [ 180 ] synthesize more GB in different compartments of chloroplasts than plants like rockcress ( Arabidopsis ) [ 181 ] and tobacco [ 182 ].…”
Section: Involvement Of Glycine Betaine Against Combinations Of Abmentioning
confidence: 99%